Pneumoperitoneum after Virtual Colonoscopy: Causes, Risk Factors, and Management. Issue 6 (June 2014) - Baccaro, Leopoldo M.; Markelov, Alexey; Wilhelm, Jakub; Bloch, Robert
Computed tomographic virtual colonoscopy (CTVC) is a safe and minimally invasive modality when compared with fiberoptic colonoscopy for evaluating the colon and rectum. We have reviewed the risks for colonic perforation by investigating the relevant literature. The objectives of this study were to assess the risk of colonic perforation during CTVC, describe risk factors, evaluate ways to reduce the incidence complications, and to review management and treatment options. A formal search of indexed publications was performed through PubMed. Search queries using keywords "CT colonography, " "CT virtual colonoscopy, " "virtual colonoscopy, " and "perforation" yielded a total of 133 articles. A total of eight case reports and four review articles were selected. Combining case reports and review articles, a total of 25 cases of colonic perforation after CTVC have been reported. Causes include, but are not limited to, diverticular disease, irritable bowel diseases, obstructive processes, malignancies, and iatrogenic injury. Both operative and nonoperative management has been described. Nonoperative management has been proven safe and successful in minimally symptomatic and stable patients. Colonic perforation after CTVC is a rare complication and very few cases have been reported. Several risk factors are recurrent in the literature and must be acknowledged at the time of the study. Management options vary and should be tailored to each individual patient.